Changes in peripheral blood in SARS CoV‐2 patients and its clinico‐pathological correlation: A prospective cross‐sectional study. (1st October 2021) - Bahadur, Shalini; Kalonia, Tushar; Kamini, Kanchan; Gupta, Bhumika; Kalhan, Shivani; Jain, Mansi
Abstract: Introduction: Coronavirus disease 2019 (COVID‐19) caused by SARS‐CoV2 can present from mild flu‐like symptoms to acute respiratory distress syndrome. There is multi‐organ involvement; particularly, hematopoietic system can be associated with morphological changes in blood cells of COVID‐19 patients. Method: We conducted a cross‐sectional study on a cohort of 50 COVID‐19 patients, confirmed on RT‐PCR with documented cycle threshold (Ct) value. Peripheral blood sample of these patients was collected and examined for complete blood counts (CBC) on automated haematological analyser as well as Leishman‐stained blood smears to look for morphological changes in blood cells. Morphological changes were evaluated with reference to clinical severity and Ct value. Additionally, association between Ct value and clinical severity was also performed. Statistical tests were performed, and P value <.05 was considered significant. Results: Mean age of our study group was 42.16 ± 15.55 years, with male preponderance. Most commonly observed peripheral blood changes were hypolobation ( P value = .002) and toxic granules ( P value = .005) in neutrophils, atypical granules with nucleolar prominence in lymphocytes, cytoplasmic granulation with clumped nuclear chromatin in monocytes, giant platelets and thrombocytopenia and normocytic normochromic anaemia. Conclusion: No association was found between clinical severity and Ct value as well as peripheral blood morphological changes with Ct value. We conclude that examination of peripheral smear coupled with complete blood count (CBC) is only partially supportive of disease pathogenesis and to assess the viral load other parameters should be utilised instead of relying solely on Ct value.